2020
DOI: 10.1038/s41467-020-14936-3
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis of human ovarian cortex identifies distinct cell populations but no oogonial stem cells

Abstract: The human ovary orchestrates sex hormone production and undergoes monthly structural changes to release mature oocytes. The outer lining of the ovary (cortex) has a key role in defining fertility in women as it harbors the ovarian reserve. It has been postulated that putative oogonial stem cells exist in the ovarian cortex and that these can be captured by DDX4 antibody isolation. Here, we report single-cell transcriptomes and cell surface antigen profiles of over 24,000 cells from high quality ovarian cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
210
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 236 publications
(225 citation statements)
references
References 63 publications
14
210
0
1
Order By: Relevance
“…In contrast, localization of CYP17A1 shifted from exclusively the theca interna in control mice to patches in the interstitial stroma in DHT-treated mice, supporting a potential role for the stroma in androgen production following certain perturbations (Candelaria et al 2019). Singlecell RNA sequencing studies have also demonstrated subpopulations of stromal cells expressing CYP17A1 and STAR (Wagner et al 2020, Wang et al 2020. Although stromal cells have demonstrated varied hormone production and responsiveness, definitive characterization of these dynamics and their functional significance remains to be established (Fig.…”
Section: R33mentioning
confidence: 95%
See 3 more Smart Citations
“…In contrast, localization of CYP17A1 shifted from exclusively the theca interna in control mice to patches in the interstitial stroma in DHT-treated mice, supporting a potential role for the stroma in androgen production following certain perturbations (Candelaria et al 2019). Singlecell RNA sequencing studies have also demonstrated subpopulations of stromal cells expressing CYP17A1 and STAR (Wagner et al 2020, Wang et al 2020. Although stromal cells have demonstrated varied hormone production and responsiveness, definitive characterization of these dynamics and their functional significance remains to be established (Fig.…”
Section: R33mentioning
confidence: 95%
“…Other studies have used DCN and LUM to identify populations of human theca/stroma cells (Fan et al 2019). Higher expression in some of the human cells considered to be stroma was demonstrated for markers PDGFRA, DCN, COL1A1, COL6A1, STAR, and/or CYP17A1 (Wagner et al 2020). A different study delineated nonhuman primate ovarian stroma by expression of TCF21, COL1A2, and/ or STAR (Wang et al 2020).…”
Section: Incompletely Characterized Stromal Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…At birth, a baby girl has per ovary approximately 300,000 primordial follicles containing immature eggs or oocytes, which constitutes the ovarian reserve [13]. The human ovarian reserve is finite, as was recently demonstrated by the lack of oocyte stem cells in single-cell analyses of adult human ovaries, demonstrating that lost oocytes cannot be replaced [14]. This clearly shows that the number of oocytes is a major limiting factor in human reproduction.…”
Section: In the Wombmentioning
confidence: 94%